해어화 - Park, Heung Sik; Han, Hyo-joo; Yoo, Yeon-seok; Park, Seong-woong; Jang, Young-nam (Ive Lotte Entertainment, 2016)
"In Imperial Japanese-occupied Korea, Jung So-yul is a gisaeng-in-training at one of the last remaining gwonbeon, learning to sing jeongga, the classical songs of Korea's upper class. Jung is the daughter of a famous gisaeng, who is also the institution's headmistress. Seo Yeon-hee arrives at the school after she is sold by her father, who cannot take care of her. The young girls become best friends, and are two of the best students in the school. They both enjoy the popular songs of the day, but promise each other to keep their dignity as the only gisaeng who sing jeongga. So-yul's natural talent and beauty make her the center of attention, and she receives invitations from important people, including the Japanese chief of police. One day in 1943, So-yul meets the top pop songwriter, Kim Yoon-woo, and the two fall in love. Yoon-woo asks So-yul to sing a song he is writing to encourage the Korean people suffering under Imperial Japanese rule. However, things begins to fall apart when he hears Yeon-hee sing and becomes mesmerized by her voice. Yoon-woo writes the song for Yeon-hee, and encourages her to leave the gwonbeon so he can help her become a pop singer, because pop songs speak more to the common people instead of just the upper class. Yeon-hee takes his advice, and So-yul feels betrayed. Fueled by jealousy, So-yul attempts to regain what she believes her friend stole from her, destroying the lives of those around her, and ultimately, herself."--Korean movie database (KMDb).